2021
DOI: 10.3390/plants10010132
|View full text |Cite
|
Sign up to set email alerts
|

The Genus Lagochilus (Lamiaceae): A Review of Its Diversity, Ethnobotany, Phytochemistry, and Pharmacology

Abstract: The genus Lagochilus (Lamiaceae) is native to Central, South-Central, and Eastern Asia. It comprises 44 species, which have been commonly used as herbal medicines for the treatments of various ailments for thousands of years, especially in Asian countries. This review aims to summarize the chemical constituents and pharmacological activities of species from the genus Lagochilus to unveil opportunities for future research. In addition, we provide some information about their traditional uses, botany, and divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…In addition to nepetalactone, Nepeta also produces glycosylated iridoids (Murai et al 1984;Formisano et al 2011;Lichman et al 2020), similar to those reported in other Lamiaceae plants (Venditti et al 2016;Fu et al 2018;Mint Evolutionary Genomics Consortium 2018;Mamadalieva et al 2021). We could identify 1,5,9 epi-deoxyloganic acid in wild type N. cataria by co-elution and comparison of a fragmentation pattern with an authentic standard.…”
Section: Discussionsupporting
confidence: 75%
“…In addition to nepetalactone, Nepeta also produces glycosylated iridoids (Murai et al 1984;Formisano et al 2011;Lichman et al 2020), similar to those reported in other Lamiaceae plants (Venditti et al 2016;Fu et al 2018;Mint Evolutionary Genomics Consortium 2018;Mamadalieva et al 2021). We could identify 1,5,9 epi-deoxyloganic acid in wild type N. cataria by co-elution and comparison of a fragmentation pattern with an authentic standard.…”
Section: Discussionsupporting
confidence: 75%
“…Plants growing in the Andean Altiplano are well known for having great natural sources of phytochemical compounds that are present in high concentrations in response to extreme environmental conditions [ 1 ]. Chilean natives have used Altiplano plants as part of their traditional medicine to treat a wide range of illnesses and ailments [ 2 , 3 , 4 ]. In this sense, native Andean Altiplano medicinal plants represent an underexplored valuable source of bioactive compounds with potential pharmacological applications [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chilean natives have used Altiplano plants as part of their traditional medicine to treat a wide range of illnesses and ailments [ 2 , 3 , 4 ]. In this sense, native Andean Altiplano medicinal plants represent an underexplored valuable source of bioactive compounds with potential pharmacological applications [ 2 , 3 , 4 ]. Among the medicinal Altiplano plants, members of the Lamiaceae and Asteraceae families have been thoroughly investigated due to their traditional uses in cooking, as aromatic plants, as well as in traditional medicine [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Southern Africa is not only known for its high levels of plant diversity (20,401 species) and plant endemism (67%) [ 7 ] but also for its cultural diversity, resulting in a rich ethnobotanical heritage. Many important aromatic, medicinal and ornamental plants have been used for centuries in traditional medicines by indigenous people across the globe [ 8 ]. A bibliography of plants used in traditional medicine in southern Africa [Arnold et al (2002)] included 215 families, equating to 3689 taxa (comprising species, subspecies and varieties) and represents ca.…”
Section: Introductionmentioning
confidence: 99%